Implementasi Manajemen Perpustakaan di SDN 1 Simo Boyolali Tahun 2016/2017 - Safitri, Risma Amelia; , Honest Ummi Kaltsum, S.S. M.Hum (2017)
This study aims to describe the implementation of library management, explain the constraints faced and describe the implementation of library management solutions in SDN 1 Simo Year 2016. Type of qualitative research with case study research design. Data collection techniques used interviews, observation, and documentation. The validity of data using source triangulation and technique. Data analysis techniques using Miles and Huberman analysis techniques include data reduction, presenting data, and drawing conclusions. The results of the discussion on the implementation of library management in SDN 1 Simo implemented in accordance with the management function including the planning has been done by establishing the vision, mission and objectives of the library, organizing in accordance with the rules of the library organization, budgeting has no definite and specific budget, or circulation, management includes inventory activities, classification, cataloging, completion and presentation, then supervision has been done and done once every year. The obstacles encountered in implementing library management include: 1) Lack of human resources in managing the library, 2) The collection of books that are less complete and less up to date because the book with the old issue is still stored on the bookshelf, 3) The absence of a budget Managed directly by the library so that the library management is less than the maximum in doubling the book collection. The efforts undertaken to overcome obstacles encountered in the implementation of library management include: 1) Headmaster recruit new workers and conduct coaching through training, workshops and comparative studies to librarians, 2) Duplication of book collections can be done through cooperation, donations and establish Budget 5-10% of school funds, 3) Funds and budgets can be submitted to the principal then submitted to the local government so that the library has a special budget to manage the library. Keywords: Implementation. library management